2009
DOI: 10.1159/000226766
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Different Expression of Molecular Markers between Cardiac Cancer and Distal Gastric Cancer and Their Correlations with Clinicopathological Features

Abstract: Background and Aim: Currently, few studies have reported the different expression of molecular markers between distal gastric cancer and cardiac cancer. Here, we sought to make an investigation about it by a retrospective analysis. Methods: The expression of 8 proteins, including epidermal growth factor receptor, glutathione S-transferase π (GST-π), cyclin D1, Neu/Her-2, C-myc, p53, p27 and p21, were evaluated in 110 cases with cardiac cancer and 101 cases with distal gastric cancer who underwent curative surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(23 reference statements)
3
0
0
Order By: Relevance
“…The immunohistochemical expression rates of p53, bcl-2, bax, and c-myc were 64.9%, 22.2%, 42.9%, 58.1%, respectively, and these results were consistent with the expression rates of other studies reported as 17–84.1%, 12.7–67%, 42.4–58.0%, 23.5–72.9%, respectively [9], [12], [22][26]. p53 played an important role in apoptosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The immunohistochemical expression rates of p53, bcl-2, bax, and c-myc were 64.9%, 22.2%, 42.9%, 58.1%, respectively, and these results were consistent with the expression rates of other studies reported as 17–84.1%, 12.7–67%, 42.4–58.0%, 23.5–72.9%, respectively [9], [12], [22][26]. p53 played an important role in apoptosis.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, a reverse correlation between p53 and histological type was found, which demonstrated that deregulation of p53 might result in uncontrolled proliferation in gastric cancer. It was consistent with a previous study [22]. It was controversy as for the prognostic value of p53, some studies have reported that p53 was associated with poor prognosis [27], [28], while others reported that p53 has no influential on prognosis [29], [30].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the expression of these proteins was investigated in 501 cases of resected primary human gastric cancers. The immunohistochemical expression rates of p53, bcl-2, bax, and c-myc were 64.9%, 22.2%, 42.9%, 58.1%, respectively, and these results were consistent with the expression rates of other studies reported as 17-84.1%, 12.7-67%, 42.4-58.0%, 23.5-72.9%, respectively [9,12,[22][23][24][25][26]. p53 played an important role in apoptosis.…”
Section: Discussionsupporting
confidence: 90%